Dissociation between the relief of skeletal pain behaviors and skin hypersensitivity in a model of bone cancer pain. Issue 6 (June 2016) - Guedon, Jean-Marc G.; Longo, Geraldine; Majuta, Lisa A.; Thomspon, Michelle L.; Fealk, Michelle N.; Mantyh, Patrick W.
Abstract : Abstract: Recent studies have suggested that in humans and animals with significant skeletal pain, changes in the mechanical hypersensitivity of the skin can be detected. However, whether measuring changes in skin hypersensitivity can be a reliable surrogate for measuring skeletal pain itself remains unclear. To explore this question, we generated skeletal pain by injecting and confining GFP-transfected NCTC 2472 osteosarcoma cells unilaterally to the femur of C3H male mice. Beginning at day 7 post-tumor injection, animals were administered vehicle, an antibody to the P2X3 receptor (anti-P2X3) or anti-NGF antibody. Pain and analgesic efficacy were then measured on days 21, 28, and 35 post-tumor injection using a battery of skeletal pain-related behaviors and von Frey assessment of mechanical hypersensitivity on the plantar surface of the hind paw. Animals with bone cancer pain treated with anti-P2X3 showed a reduction in skin hypersensitivity but no attenuation of skeletal pain behaviors, whereas animals with bone cancer pain treated with anti-NGF showed a reduction in both skin hypersensitivity and skeletal pain behaviors. These results suggest that although bone cancer can induce significant skeletal pain-related behaviors and hypersensitivity of the skin, relief of hypersensitivity of the skin is not always accompanied by attenuation of skeletal pain. Understanding the relationship between skeletal and skin pain may provide insight into how pain is processed and integrated and help define the preclinical measures of skeletal pain that are predictive end points for clinical trials. Abstract : Supplemental Digital Content is Available in the Text.Skeletal pain can induce skin hypersensitivity but analgesics may relieve the skin hypersensitivity without relieving the underlying skeletal pain.